Oxaliplatin toxicity presenting as a liver nodule - case report - Alexandrino, Henrique (2015)
Background: Oxaliplatin based chemotherapy is often used as adjuvant therapy in colon and rectal cancer. A reported side effect is Sinusoidal Obstruction Syndrome which is characterized by a spectrum of pathologic changes, from sinusoidal dilation, peri-sinusoidal haemorrhage, peliosis and nodular regenerative hyperplasia. Very rarely it can cause the development of liver nodules mimicking liver metastases. Herein, we report a case of Sinusoidal Obstruction Syndrome causing a liver nodule suspicious of liver metastasis on imaging. This is the third reported case of this complication of oxaliplatin toxicity, in which resection was performed and pathological diagnosis confirmed. Case presentation: We report the case of a 59 year old man with stage III colon cancer who underwent sigmoidectomy followed by adjuvant chemotherapy with oxaliplatin. One year after surgery a liver nodule was detected and the patient underwent right hepatectomy. Pathology showed no liver nodule and diagnosed sinusoidal obstruction syndrome. Conclusion: We describe the third reported case of a liver lesion mimicking a liver metastasis after oxaliplatin-based chemotherapy for colon cancer. We suggest that in patients heavily treated with oxaliplatin with de novo liver nodules, this differential diagnosis should be considered. In particular, in this population of patients an intense imagiologic evaluation and even a preoperative biopsy should be pursued to confirm the diagnosis of malignancy and avoid overtreatment.